Comparison of Endoscopic Submucosal Dissection and Surgery for Differentiated Type Early Gastric Cancer within the Expanded Criteria - Dong Woo Shin; Hee Young Hwang; Seong Woo Jeon (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims Endoscopic submucosal dissection (ESD) is a novel alternative treatment for differentiated early gastric cancer (EGC) without lymph node metastasis. We conducted this study to verify the therapeutic usefulness of ESD for treating differentiated EGC compared to that of surgery. Methods This is a retrospective cohort study of 382 patients treated with differentiated EGC from March 2006 to May 2010. The propensity score yielded 275 matched patients. They were divided into an ESD group of 175 people and a gastrectomy group of 100 people. The patient demographics, pathologic characteristics, length of hospital stay, complication rate and survival rate were compared. Results The complication rate was higher for the gastrectomy group than for the ESD group (15.0% vs. 5.1%, p=0.007). The average length of patient hospitalization was longer after gastrectomy than after ESD (8.6 days vs. 2.4 days, p<0.001). There were two cases of mortality in the surgery group within 30 days of procedure. The 5-year survival rates of the two groups did not show a statistically significant difference (92.0% vs. 93.3%, p=0.496). Conclusions The long-term survival rates of ESD and gastrectomy were not significantly different. The complication rate was lower for ESD than for gastrectomy, and the length of hospital stay was shorter after ESD than after gastrectomy.